O desenvolvimento profissional corresponsável na (re)estruturação da identidade docente em letras - Gatto, Vanessa Bianchi (2019)
Co-responsible Professional Development (CPD) is the name given by the Holistic Activity Theory to its proposal for initial and continued training for Languages professionals. It is a horizontal triangulation between academic and market professionals who share the same work framework (the same language teaching paradigm, in this case). It can focus on core activities (linguodidactics), when the clientele is included in the alliance; or the supporting activities (resource training), when a Languages graduate is part of the alliance. The objective of this study is to analyze the role that CPD plays in restructuring the professional ego of the language educator, which is currently fragmented. To this end, the author develops action research in which she herself, advised by a team of professional peers, intervenes in her context and professional practice in the three roles that she progressively starts to perform in a CPD nucleus: market teacher, academy supervisor and researcher. In this research, therefore, the distance between subject and object as well as classic scientific impartiality give way to a critical and self-critical vision that allows the author to evaluate the effects of CPD on the construction of her own teaching identity and the integration of her professional role. The data analyzed emerge from the aforementioned CPD context and correspond mainly to records (written and transcribed) of framing listening (online and in person), which is its central discursive genre. However, some satellite genres produced in the same context are triangulated in the analysis, such as parallel testimonies, teaching materials and evaluation worksheets. The research corpus, therefore, comprises the linear record of discursive and practical activities carried out in the linguistic, supervisory and investigative spheres over three years of CPD. Data selection is based on the Evidence Paradigm, which allows tracking signs of progressive professional growth, and its interpretation is carried out in light of version 5.0 of the Holistic Activity Theory, which emphasizes the epistemological and ethical dimensions necessary for consolidation of the professional role of the linguistic educator. The results point, initially, to the emergence of a practical rationality and professional ethics, resulting from the framing listening carried out in the context of CPD-end, given the signs of the progressive framing of the teacher's linguodidactic act. In a second moment, and as a corollary of the first, they highlight the development of theoretical rationality and ethics, resulting from the progressive framing self-listening in the CPD-medium, as revealed by the signs of selfmonitoring in the supervisor's framing act. And, finally, and also as a corollary of the previous result, they point to an intrinsic proto-rationality latent in the scientific activity developed in the CPD-metatheoretical, given the evidence of the integration of logical and historical rationalities in the researcher's investigative act. In conclusion, CPD played a decisive role in the integration of the teaching role, since, by acting as a starting point and considering aspects of affectivity, it gave the professional the mastery to progressively frame her work, monitor its framing and improve it scientifically, thus establishing the foundations for the consolidation of an intrinsic rationality. The importance of a more historicist epistemology in Languages is highlighted (to the detriment of a tout-court theoretical-logical one), as the CPD course proves that we only really know what is produced materially at a given moment in History, so that the profession that emerges from the cognition of the linguistic educator is one that results from practice, from the material collective, situated and dated. In practice, what is urgent is the need for professional peers to join CPD centers, until Associations capable of requesting Regulations (Professional Council and Code of Ethics) are consolidated, a sine qua non condition for the intrinsic rationality germinated in the triangulation. A new History of the Teaching Profession in Languages, constructed and told by the professionals themselves, will only be possible when these professionals, united by common values-conductthoughts, take new steps, create new facts in the direction of autopoiesis and record them. This is what the author of this research does.